Deberes y derechos prescritos en la constitución y la ley del anciano sobre los adultos mayores - Toapanta Masabanda, José Washington (2015)
The draft legal research entitled "Duties and rights enshrined in the constitution and Elder Law on the elderly" was to verify the level of knowledge that older adults are immersed in the Holy Family Gerontology Center La Maná Canton because 90% of them are unaware of the content of their rights enshrined in the Constitution and laws. As such, it is intended to present as a solution to this problem, the creation of a manual on duties and rights of the Elderly, for they and their families know about these and they can forewarn and generate a better quality of life Such shortcomings was made through research techniques and methods that help you get the most evidence to better conceptualize the object of study, same that began with a survey of those involved, which subsequently analyzed for the conclusions on the issues presented. At the same time it is able to conclude that older adults know little or nothing about their rights and duties, and they are not grouped in one body and in order, but are scattered in the Constitution and the Law on the Elderly. Know neither the rights pertaining to them, framed worse in other legislation, as the country is enrumbada to conquer the Sumak Kawsay for everyone, and it is the duty of society in this social program include the elderly and got everything, it is expected that this project will serve to teachers, students and society in order to achieve a better living.